Police Code of Silence in Times of Change - Kutnjak Ivković, Sanja; Maskály, Jon; Kule, Ahmet; Haberfeld, Maria Maki (SpringerBriefs in Policing,, 2022)
This book explores the contours of the code of silence and provides policy recommendations geared toward creating an environment less conducive for police misconduct. It responds to the recent calls for police reform, in the wake of the perceived illegitimacy of police actions and the protection that the code of silence seems to provide to the police officers who violate the official rules.Using a case study of a medium-sized U.S. police agency, this book employs the lens of police integrity theory to provide empirically grounded explanations of the code of silence. It examines the potential effects of organizational factors and the attitudes of individual police officers on their willingness to adhere to the code of silence in cases of police corruption, the use of excessive force, interpersonal deviance, and organizational deviance. The book focuses on the following factors that could influence the police code of silence in the times of change: The impact of organizational rule dissemination, discipline, and disciplinary fairness on the scope of the code of silence The role organizational justice plays in shaping police officer willingness to report misconduct The effect that police officers' self-legitimacy has on their decisions to adhere to the code The influence of peer culture on individual police officer amenability to maintain the code The relationship between officers' views of themselves, the organization, and the community on their willingness to report misconduct .